Can Strategic Litigation Backfire? Challenging the Crackdown on Migration NGOs in Greece Through EU Law - Elli Kriona Saranti (German Law Journal)
In 2020, amid aggressive and inflammatory political discourse and an unprecedented wave of violent attacks against migration Non-Governmental Organizations and their staff, the Greek Government sought to establish a new legal framework for the registration of Non-Governmental Organizations active in the fields of international protection, migration and social inclusion, and their members. This Article aims at providing an overview of the EU-law based litigation brought by Greek Civil Society organizations to challenge the new framework for breaching fundamental rights, and at exploring its effects beyond the Court proceedings. This Article concludes that, counterintuitively, the existence of pending litigation against the Regulation establishing the NGO Registries hampered advocacy on this issue with the European Commission.